2019
DOI: 10.1155/2019/1692104
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Unfavorable Outcomes in Patients with Atrial Fibrillation and Concomitant Heart Failure with Different Ejection Fractions: RIF-CHF Register One-Year Follow-Up

Abstract: Background. Atrial fibrillation (AF) and heart failure (HF) are tightly interrelated. The concurrence of these pathologies can aggravate the pathological process. The geographic and ethnic characteristics of patients may significantly affect the efficacy of different types of therapy and patients’ compliance. The objective of this study was to analyze how the features of the course of the diseases and management of HF + AF influence the clinical outcomes. Methods. The data of 1,003 patients from the first Russ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The risk of mortality was similar in patients with HFpEF and HFmrEF. The risks of mortality in patients with AF and HF have been discussed in several clinical trials, including patients with all types of HF [ 23 , 32 , 33 ]. The majority of the studies concluded that the association of the two conditions leads to the increase of mortality risk compared to the individual risk of each disease alone [ 23 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of mortality was similar in patients with HFpEF and HFmrEF. The risks of mortality in patients with AF and HF have been discussed in several clinical trials, including patients with all types of HF [ 23 , 32 , 33 ]. The majority of the studies concluded that the association of the two conditions leads to the increase of mortality risk compared to the individual risk of each disease alone [ 23 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…AF often occurs as a cause or consequence of HF [ 15 , 16 ]. Adverse outcomes are worse when AF and HF coexist [ 17 , 18 ]. In this regard, future studies are needed to identify sex-related differences in the prevalence and outcomes of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two meta-analyses have reported that the coexistence of AF in HF patients increased the odds of mortality from 14% to 57% when compared to HF alone [ 16 , 17 ]. AF is also associated with an increased risk of readmission for HF exacerbation [ 18 , 19 , 20 ]. However, previous studies have mainly focused on the impact of AF on mortality in HF patients when compared to hospital readmission rates and ER visits as a quality of care indicator [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…22) Several studies have documented that severe tachycardia per se or tachycardia with atrial fibrillation worsens LV function and increases mortality and morbidity in patients with dHF. [1][2][3][4][5] Currently, therapeutic options for patients with heart failure and tachycardia suggest the use of β-blockers to restore or maintain sinus heart rhythm, or to decrease the ventricular response rate in chronic atrial fibrillation. 4,8) Landiolol is a highly effec-tive β-blocker for controlling heart rhythm without any vasodilatory effect because it is ultra-short-acting and quickly metabolized.…”
Section: Discussionmentioning
confidence: 99%
“…T achycardias including supraventricular tachyarrhythmias such as atrial fibrillation are frequently observed in patients with decompensated heart failure (dHF), increasing the risk of mortality. 1,2) The development of atrial tachyarrhythmia is often associated with an irregular ventricular rhythm and an absence of an atrial kick, leading to a decrease in cardiac output with consequent worsening of cardiac hemodynamic function. [1][2][3][4][5] Therefore, the normalization of heart rhythm or rate can often play a crucial role in the correction of cardiac dysfunction.…”
mentioning
confidence: 99%